Serotonin and the 5‐HT7 receptor: The link between hepatocytes, IGF‐1 and small intestinal neuroendocrine tumors. Issue 7 (24th May 2013) - Svejda, Bernhard; Kidd, Mark; Timberlake, Andrew; Harry, Kathy; Kazberouk, Alexander; Schimmack, Simon; Lawrence, Ben; Pfragner, Roswitha; Modlin, Irvin M.
Abstract : Platelet‐derived serotonin (5‐HT) is involved in liver regeneration. The liver is also the metastatic site for malignant enterochromaffin (EC) cell "carcinoid" (neuroendocrine) neoplasms, the principal cellular source of 5‐HT. We hypothesized that 5‐HT produced by metastatic EC cells played a role in the hepatic tumor‐microenvironment principally via 5‐HT7 receptor‐mediated activation of hepatocyte IGF‐1 synthesis and secretion. Using isolated rat hepatocytes, we evaluated 5‐HT7 receptor expression (using PCR, sequencing and western blot). ELISA, cell transfection and western blots delineated 5‐HT‐mediated signaling pathways (pCREB, AKT and ERK). IGF‐1 synthesis/secretion was evaluated using QPCR and ELISA. IGF‐1 was tested on small intestinal neuroendocrine neoplasm proliferation, while IGF‐1 production and 5‐HT7 expression were examined in an in vivo SCID metastasis model. Our results demonstrated evidence for a functional 5‐HT7 receptor. 5‐HT activated cAMP/PKA activity, pCREB (130–205%, P < 0.05) and pERK/pAKT (1.2–1.75, P < 0.05). Signaling was reversed by the 5‐HT7 receptor antagonist SB269970. IGF‐1 significantly stimulated proliferation of two small intestinal neuroendocrine neoplasm cell lines (EC50 : 7–70 pg/mL) and could be reversed by the small molecule inhibitor BMS‐754807. IGF‐1 and 5‐HT were elevated (40–300×) in peri‐tumoral hepatic tissue in nude mice, while 5‐HT7 was increased fourfold compared to sham‐operated animals. We conclude that hepatocytes express a cAMP‐coupled 5‐HT7 receptor, which, at elevated 5‐HT concentrations that occur in liver metastases, signals via CREB/AKT and is linked to IGF‐1 synthesis and secretion. Because IGF‐1 regulates NEN proliferation, identification of a role for 5‐HT7 in the hepatic metastatic tumor microenvironment suggests the potential for novel therapeutic strategies for amine‐producing mid‐gut tumors.